Association of the aromatase gene with Alzheimer's disease in women. - Butler, H; Warden, DR; Hogervorst, E; Ragoussis, J; Smith, A; Lehmann, D (2010)
Associations have been reported of aromatase polymorphisms with Alzheimer's disease (AD). We studied nine polymorphisms in 207 cases of AD, 23 cases of mild cognitive impairment (MCI) and 233 controls, all from the OPTIMA cohort. We replicated two reported associations and found others. Our findings were consistent between AD and MCI. Further, our results were sex-specific, i.e. there were significant interactions between certain polymorphisms and gender, and the associations with AD were almost entirely in women. Aromatase catalyses the conversion of androgens to estrogens. It is expressed in the human brain. In the hippocampus, it is upregulated in postmenopausal women and is lowered in AD. These sex-specific results are therefore plausible. However, our results now need to be replicated in a larger dataset.